Analysis Of Factors Influencing Consumer Purchasing Decisions On The Residential Area Of Pt Verona Hils Cirebon - Mar’atus Solikhah; Vika Faransisca; Khofifah Indah Baitul Jannah (Journal Research of Social Science, Economics, and Management, 2024)
This study conducts an analysis of factors influencing consumer purchasing decisions in the residential area of PT Verona Hills Cirebon. The research aims to identify and understand the key determinants that play a significant role in shaping consumers' choices when making property purchases in this specific locality. Utilizing a comprehensive approach, the study examines various factors such as market trends, pricing strategies, location preferences, and overall consumer behavior. The findings from this analysis contribute valuable insights to real estate professionals, developers, and policymakers involved in the residential property market, aiding them in devising effective strategies to meet consumer needs and enhance the overall attractiveness of the PT Verona Hills Cirebon residential area.